Highly efficient catalyst derived from Ni-Fe-hydrotalcite for solvent-free O- or S-acetylation of alcohols, phenols and thiols at room temperature - Choudhary, Vasant R. (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2013)
Solvent-free O-acetylation of alcohols (including secondary and tertiary alcohols) and phenols and S- acetylation of thiols by acetyl chloride with high product yields at room temperature in a very short reaction period can be easily accomplished using a small amount of solid catalyst obtained from the decomposition (at 600 A degrees C) of Ni-Fe-hydrotalcite. Both the reactions are carried out at room temperature under solvent-free conditions. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity.
Keywords: Acetyl chloride; Alcohols; Ni-Fe- ht derived catalyst; O- and S-acetylation; Phenols; Solvent-free